2014
DOI: 10.1620/tjem.232.177
|View full text |Cite
|
Sign up to set email alerts
|

U-Shape Relationship of White Blood Cells with Acute Kidney Injury and Mortality in Critically Ill Patients

Abstract: Low or high counts of white blood cells (WBCs) and WBC subtypes can be a predictor of morbidity and mortality in several clinical settings. However, the correlations of WBC and its subtypes with acute kidney injury (AKI) and mortality remain unresolved in critically ill patients. The counts of WBC and subtypes, such as neutrophil, lymphocyte, monocyte, and eosinophil, were measured in 2,079 patients admitted to the intensive care unit (ICU) from June 2004 through June 2010. The non-linear relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The presence of neutrophils has proven to be a predictor of morbidity and mortality in several clinical settings. 15 However, few studies have determined the correlation between neutrophil counts and AKI, and the linear relationship observed between neutrophil counts and AKI is consistent with a previous report, 28 which found a U-shaped relationship between white blood cells (WBCs) and AKI in critically ill patients. When these authors analyzed the relationships between subtypes of WBCs and AKI, the adjusted ORs associated with a quartile increase in neutrophils (and no other WBC subtype) were 0.99 (95% CI, 0.71–1.40), 0.83 (95% CI, 0.59–1.16), 1 (Reference), 1.23 (95% CI, 0.87–1.75), and 1.69 (95% CI, 1.41–2.51).…”
Section: Discussionsupporting
confidence: 86%
“…The presence of neutrophils has proven to be a predictor of morbidity and mortality in several clinical settings. 15 However, few studies have determined the correlation between neutrophil counts and AKI, and the linear relationship observed between neutrophil counts and AKI is consistent with a previous report, 28 which found a U-shaped relationship between white blood cells (WBCs) and AKI in critically ill patients. When these authors analyzed the relationships between subtypes of WBCs and AKI, the adjusted ORs associated with a quartile increase in neutrophils (and no other WBC subtype) were 0.99 (95% CI, 0.71–1.40), 0.83 (95% CI, 0.59–1.16), 1 (Reference), 1.23 (95% CI, 0.87–1.75), and 1.69 (95% CI, 1.41–2.51).…”
Section: Discussionsupporting
confidence: 86%
“…Several inflammatory biomarkers including white blood cell (WBC) count, leukocyte subtypes, platelet, CRP, NLR and PLR have been demonstrated to be important prognostic predictors in various cardiovascular diseases [ 14 ] . Each WBC subtype, including neutrophils, lymphocytes, monocytes, and eosinophils, has a discrete role in inflammation, host defense, and repair [ 15 ] . Each of these components are one of the immunologic factors that play a pivotal role in most processes of organ damage and this role can apply to the issue of kidney damage [ 16 ] .…”
Section: Discussionmentioning
confidence: 99%
“…First, frail patients and patients with AKI had similar characteristics including high WBC and low body mass index, hemoglobin, and albumin levels (Tables 1 and 2 ). Previous studies reported that a high WBC/body mass index is associated with AKI in critically ill patients[ 23 , 24 ]. Hypoalbuminemia and anemia were also reported to be independently associated with AKI[ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%